+0  
 
0
30
1
avatar

Attempt to derive the formula for the sum of two cubes. (Proof)

 
Guest Sep 16, 2017
social bar
Sort: 

1+0 Answers

 #1
avatar+76102 
+2

 

Note

 

(a + b)^3   =  a^3  + 3a^2b + 3ab^2 + b^3

 

(a + b) ^3  = a^3 + 3ab (a + b) + b^3 

 

(a + b) ^3   -   3ab (a + b)  =  a^3  + b^3

 

(a + b)  [( a + b)^2 - 3ab ]  = a^3 + b^3

 

(a + b) ( a^2 + 2ab + b^2 - 3ab)  = a^3 + b^3

 

(a + b) ( a^2 - ab + b^2 )  = a^3 + b^3

 

 

cool cool cool

 
CPhill  Sep 16, 2017

28 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details